Tata Laksana Vaskulitis Kulit: Tinjauan Pustaka - Devina, Wilona; Saraswati, Putu Dyah Ayu (PT Kalbe Farma Tbk., 2026)
Cutaneous vasculitis represents a heterogeneous group of inflammatory disorders characterized by inflammation of the cutaneous blood vessel walls and surrounding perivascular tissue, with highly variable clinical manifestations depending on the size and anatomical location of the affected vessels. This condition may present as a disease limited to the skin or as part of a systemic disorder. Epidemiologically, cutaneous vasculitis can occur at all ages but is more frequently observed in adults, whereas in children it is generally self-limiting, with IgA vasculitis being the most common subtype. The etiology of cutaneous vasculitis is predominantly idiopathic; however, infections, medications, autoimmune diseases, and malignancies may also contribute. The pathogenesis involves immune complex deposition and mechanisms mediated by anti-neutrophil cytoplasmic antibodies (ANCA), leading to endothelial injury and vascular inflammation. The main clinical manifestation is palpable purpura, typically distributed symmetrically on the lower extremities, accompanied by various additional skin lesions such as papules, nodules, vesicles, and ulcers. Diagnosis is established through skin biopsy, which remains the gold standard, including histopathological examination and direct immunofluorescence. Most cases are mild and resolve spontaneously; however, systemic therapy is required in severe, chronic, or recurrent conditions. Overall, the prognosis of cutaneous vasculitis is favorable, with a low risk of progression to systemic vasculitis when appropriate diagnosis and management are implemented.